The Interplay of Foreign Policy and Democratic Erosion - Thapa, Santa Bahadur (DEPAN, 2024)
This paper investigates the intricate relationship between foreign policy and the vitality of democratic systems. It argues that a nation’s foreign policy choices can fortify or erode its democratic foundations. The paper analyzes how misguided foreign policy decisions contribute to the decay of democratic norms and institutions. Employing a case study approach, it examines four critical instances of foreign policy missteps: the U.S. intervention in Iraq, Russia’s actions in Ukraine, Saudi Arabia’s involvement in Yemen, and China’s assertive stance in the Indo-Pacific. The paper reveals how such foreign policy choices have fueled democratic decline within these nations and destabilized international norms. The repercussions of these missteps extend beyond domestic turmoil and economic instability, potentially damaging a nation’s global reputation and eroding public trust. The findings emphasize the crucial need to ground foreign policy in democratic values. Respecting human rights and engaging with the international community are not merely idealistic pursuits but vital strategies for preserving democracy, promoting prosperity, and fostering global peace. By aligning foreign policy with democratic principles, nations can strengthen their democratic institutions and contribute to a more stable and cooperative world order.